PENGARUH STRES KERJA, KOMPENSASI DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA UNIT LAYANAN PENGADAAN BARANG DAN JASA LINGKUP PEMERINTAH KOTA BIMA - M. Syukur Dwiriansyah; Meutia Meutia; Heriani Heriani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to analyze the effect of work stress, compensation and work discipline on job satisfaction of employees of the Unit Layanan Pengadaan (ULP) Barang dan Jasa Pemerintah Kota Bima. Referring to the level of explanation, this research is classified into associative research. Respondents in this study were employees of the ULP for the procurement of goods/services of the Bima City Government and the Pokja totaled 36 employees at the Procurement Service Unit (ULP) of the Bima City Government. The research instrument used a questionnaire using a Likert scale and the data were analyzed using multiple linear regression analysis with the help of the SPSS program. The results of this study indicate that (1) the lower the work stress, the higher the job satisfaction; (2) the higher the compensation, the higher the job satisfaction; (3) the better the level of work discipline, the higher the level of job satisfaction. (4) Work stress, compensation and work discipline have a significant simultaneous effect on job satisfaction. Therefore, it is better to take policies to increase employee job satisfaction, especially in the Goods and Services Procurement Service Unit of the City of Bima City Government should pay attention to work patterns as an effort to reduce high work stress and compensation adjustments and increase work discipline because it will affect job satisfaction.